The Cambridge introduction to Anglo-Saxon literature - Magennis, Hugh. (Cambridge ; New York : Cambridge University Press, 2011)
"An approachable and stimulating introduction to Anglo-Saxon literature, this book provides indispensable guidance for students on this important and rewarding area of literary studies. The chapters are clearly organised by topic and significant attention is paid to key individual works, including Beowulf, The Seafarer and writings by Bede. All textual quotations are translated into modern English, with the original language texts carefully explained. The Introduction synthesises and develops dominant approaches to Anglo-Saxon literature today, integrating Old English and Latin traditions, and placing the literature in larger historical and theoretical contexts. The structure, style and layout is attractive and user-friendly, including illustrative figures and textboxes, and Magennis provides guidance on resources for studying Anglo-Saxon literature, informing the reader of opportunities for investigating the subject further. Overall, the book enables a thorough understanding and appreciation of artful and eloquent works from a distant past, which still speak powerfully to people today"--
Machine generated contents note: 1. Approaching Anglo-Saxon literature; 2. Literary traditions; 3. Varieties of narrative; 4. Belief, knowledge, experience: some non-narrative strands; 5. Anglo-Saxon afterlives, medieval to modern: later uses and appropriations of Anglo-Saxon writings; Appendix: resources for studying Anglo-Saxon literature, Bibliography.
Includes bibliographical references (p. 195-211) and index.
Keywords: English literature -- Old English, ca. 450-1100 -- History and criticism; Civilization, Anglo-Saxon, in literature; Civilization, Medieval, in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh